Toward a Standardized Test of Fearful Temperament in Primates: A Sensitive Alternative to the Human Intruder Task for Laboratory-Housed Rhesus Macaques (Macaca mulatta) - Bethell, Emily J.; Cassidy, Lauren C.; Brockhausen, Ralf R.; Pfefferle, Dana (Frontiers in Psychology, 2019)
Standardised and sensitive tests to assess differences in temperament among primates housed in captivity are essential for monitoring welfare and improving science outcomes through reduced noise in data. Fearful temperament in primates has traditionally been assessed using the Human Intruder Test (HIT) in which duration of bodily freeze in response to approach by an unknown human is measured. The HIT is susceptible to variation between facilities in execution, interpretation of data and could be stressful for animals with more fearful temperaments. We tested the applicability of a touch-screen task with putatively negative stimuli as a more standardisable and sensitive tool for measuring fearful temperament in laboratory primates. Seventeen adult male rhesus macaques were assessed for fearfulness using the HIT. They were then tested on a touch-screen task designed to measure two behavioural indices of fearfulness: behavioural inhibition and response-slowing. We predicted monkeys assessed as having more fearful temperament in the HIT, would show the greatest degree of behavioural inhibition and response-slowing to negative pictures in the touch-screen task. In Study 1 monkeys were rewarded with juice for touching grey squares on the screen (control trials). On test trials a picture of an unknown male conspecific face with direct-gaze (signalling threat) was shown. Monkeys were less likely to touch direct-gaze faces than control trials, indicating behavioural inhibition to threat. Behavioural inhibition was greatest amongst monkeys scored with most fearful temperament in the HIT. This primary result indicates the touch-screen task may be sensitive to a more subtle form of the bodily freeze behaviour measured using the HIT. In Study 2, we tested whether these findings generalized to other classes of putatively negative stimuli; monkeys were shown pictures of the human intruder and objects associated with veterinary and husbandry procedures, interspersed with control trials (grey squares). There was no evidence of behavioural inhibition in Study 2. There was some evidence for response-slowing, which was greater for pictures of objects than pictures of the human intruder, and occurred independently of fearfulness in the HIT. We propose touch-screen tasks provide a more standardised and sensitive approach for assessing fearful temperament in laboratory primates.